2005
DOI: 10.1002/pssa.200461466
|View full text |Cite
|
Sign up to set email alerts
|

High‐current AlInN/GaN field effect transistors

Abstract: We present a study on AlInN/GaN field effect transistors (FETs) grown by metalorganic chemical vapor phase epitaxy. AlInN can be grown lattice‐matched to GaN with an In concentration of 18%. In this study samples with In concentrations ranging from 9.5 to 24%, covering a range from tensely to compressively strained AlInN layers, were grown on GaN layers on Si(111). From Hall effect and capacitance‐voltage measurements we find high sheet carrier densities for most of the samples indicating a high electron densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…However, reports on AlInN and AlInN/GaN heterostructures in the literature are rapidly increasing. [14][15][16][17][18] Recently, Gonschorek et al 5 reported a mobility value of 1170 cm 2 / V s along with 2.6ϫ 10 13 cm -2 2DEG density for an undoped nearly lattice-matched AlInN/AlN/GaN heterostructure. The corresponding two-dimensional sheet resistance was reported as 210 ⍀ / ᮀ.…”
Section: Introductionmentioning
confidence: 99%
“…However, reports on AlInN and AlInN/GaN heterostructures in the literature are rapidly increasing. [14][15][16][17][18] Recently, Gonschorek et al 5 reported a mobility value of 1170 cm 2 / V s along with 2.6ϫ 10 13 cm -2 2DEG density for an undoped nearly lattice-matched AlInN/AlN/GaN heterostructure. The corresponding two-dimensional sheet resistance was reported as 210 ⍀ / ᮀ.…”
Section: Introductionmentioning
confidence: 99%
“…The spike thickness was varied from 1 nm (blue) to 1.8 nm (red) and to 2.3 nm (pink) while the sum of barrier and spike thickness was kept constant. For an increasing spike thickness a shift of the hump between the GaN and AlN peak to higher angles appears as already denoted in [3]. The comparison with our measurement data limits the probable thickness range to 0.8 nm to 1.2 nm.…”
Section: Methodsmentioning
confidence: 63%
“…Attractive for high frequency and high power applications, AlGaN/GaN-based high electron mobility transistors (HEMT) have been the focus of research for several years now and have thus been developed to a reasonable level of maturity [1][2][3]. A promising new approach to improve the performance of such devices is to replace the AlGaN barrier layers with AlInN.…”
mentioning
confidence: 99%
“…(2) As Al 0.83 In 0.17 N and GaN are lattice matched, there are no mechanical constraints in the epitaxial structures. These mechanical constraints are harmful to the reliability of the devices and are also supposed to be at the origin of trapping centers in transistors [7][8][9].…”
Section: Introductionmentioning
confidence: 99%